Context, culture and critical thinking: Scottish secondary school teachers' and pupils' experiences of outdoor learning. (23rd October 2015) - Christie, Beth; Beames, Simon; Higgins, Peter
Abstract : Limited research exists that considers the usefulness of outdoor learning as a legitimate pedagogical approach for the delivery of a mainstream secondary school curriculum. To address this shortcoming, we investigated the ways in which mathematics and geography teachers and students from three secondary schools in Scotland responded to the Outdoor Journeys programme, which is a school‐based teaching approach that enables pupils to learn about the people and place in which they live. Data collection included participant observation, short questionnaires and interviews with approximately 150 students (11–14 years old) and 10 teachers. In most cases, pupils enjoyed the opportunity to guide their own learning experientially and beyond the familiar classroom context. Teachers acknowledged that such an approach presented an opportunity to develop pupils' critical thinking skills and that these skills can, in some cases, be overlooked in early secondary education. Following these findings, we discuss the pedagogical implications arising from the inclusion of critical thinking as a key outcome of outdoor learning, and as part of the Outdoor Journeys programme, within a secondary school context. We continue by adding our voice to the nascent literature addressing outdoor learning approaches that seek to gain traction within the broader social ecology of established school cultures.